2018
DOI: 10.1042/bsr20181799
|View full text |Cite
|
Sign up to set email alerts
|

Maggot protein ameliorates dextran sulphate sodium-induced ulcerative colitis in mice

Abstract: Ulcerative colitis (UC) is a common chronic remitting disease but without satisfactory treatment. Maggots are known as a traditional Chinese medicine named as ‘wu gu chong’. The aim of the present study was to investigate the therapeutic effect of the maggot protein on dextran sulphate sodium (DSS)-induced colitis in C57BL/6 mice. In the present study, female C57BL/6 mice were given sterile water containing 3% DSS to establish the model of UC. Mice were randomly divided into five groups: control group (sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…Our data clearly demonstrated that the maggot extracts alleviated inflammation and oxidative stress in experimental colitis via modulation of the Nrf2/HO-1 pathway. While contributions of the maggot extracts to anti-inflammation have been recognized in our previous study [46], the molecular basis accounting for the function of the maggot extracts has not been elucidated. In this study, two important points have been clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Our data clearly demonstrated that the maggot extracts alleviated inflammation and oxidative stress in experimental colitis via modulation of the Nrf2/HO-1 pathway. While contributions of the maggot extracts to anti-inflammation have been recognized in our previous study [46], the molecular basis accounting for the function of the maggot extracts has not been elucidated. In this study, two important points have been clarified.…”
Section: Discussionmentioning
confidence: 97%
“…During the entire experimental period, the activity, physiological status and body weight were monitored daily. The status of the UC mice was scored using the disease activity index (DAI) according to the degree of weight loss, fecal viscosity and bleeding ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…The volumes of distilled water or DSS solution consumed by all of the animals were measured daily, and there were no significant differences in water consumption among the groups. HQD and ME were administered daily by oral gavage (Chen et al, 2016;Wang et al, 2018).…”
Section: Experimental Animals and Groupingmentioning
confidence: 99%